Wakaf Tunai: Pencapaian Pendidikan Tinggi Berkualitas - Irwan Fauzy Ridwan (LPPM IAIT, 2023)
Quality education determines the quality of human resources, and quality human resources play an important role in achieving sustainable development. Higher education has an important role in realizing quality human resources by organizing education, research, and community service, which is called the Tridharma of higher education. The philanthropic potential of the Indonesian nation cannot be underestimated as leverage for achieving Advanced Indonesia in 2045. Waqf money as one of the philanthropic instruments is expected to be an alternative in realizing the achievement of the Sustainable Development Goals (SDGs) by 2030, in this case the target of quality education in higher education. The purpose of this study is to find an appropriate cash waqf utilization strategy in accelerating the achievement of quality higher education in accordance with the Sustainable Development Goals (SDGs). This research uses a qualitative method with a descriptive analysis approach, which describes the utilization of cash waqf in realizing quality education. This study found that the utilization of Cash Waqf in the field of education, both in the form of cash waqf and waqf through money, has great potential to build the independence of universities in organizing higher education, so as to improve the quality of higher education while providing opportunities for the community to participate in higher education in Indonesia